Enhanced Efficiency of Hot‐Cast Large‐Area Planar Perovskite Solar Cells/Modules Having Controlled Chloride Incorporation. Issue 8 (20th December 2016) - Liao, Hsueh‐Chung; Guo, Peijun; Hsu, Che‐Pu; Lin, Ma; Wang, Binghao; Zeng, Li; Huang, Wei; Soe, Chan Myae Myae; Su, Wei‐Fang; Bedzyk, Michael J.; Wasielewski, Michael R.; Facchetti, Antonio; et al.
Abstract : Organic–inorganic perovskite photovoltaics are an emerging solar technology. Developing materials and processing techniques that can be implemented in large‐scale manufacturing is extremely important for realizing the potential of commercialization. Here we report a hot‐casting process with controlled Cl − incorporation which enables high stability and high power‐conversion‐efficiencies (PCEs) of 18.2% for small area (0.09 cm 2 ) and 15.4% for large‐area (≈1 cm 2 ) single solar cells. The enhanced performance versus tri‐iodide perovskites can be ascribed to longer carrier diffusion lengths, improved uniformity of the perovskite film morphology, favorable perovskite crystallite orientation, a halide concentration gradient in the perovskite film, and reduced recombination by introducing Cl − . Additionally, Cl − improves the device stability by passivating the reaction between I − and the silver electrode. High‐quality thin films deployed over a large‐area 5 cm × 5 cm eight‐cell module have been fabricated and exhibit an active‐area PCE of 12.0%. The feasibility of material and processing strategies in industrial large‐scale coating techniques is then shown by demonstrating a "dip‐coating" process which shows promise for large throughput production of perovskite solar modules. Abstract : A hot‐casting perovskite processing technique with controlled Cl − incorporation affords a high power conversion efficiency of 18.2% for small‐area (0.09 cm 2 ), 15.4% for large‐area (≈1 cm 2 ) single solar cells, and 12.0% for large‐area 5 cm × 5 cm eight‐cell modules and compatibility with large throughput production techniques.